Literature Review: Green Computing For Environmental Sustainability - Rohmah, Mufidatur (Information Technology International Journal, 2023)
This research aims to provide an overview of Green IT to improve performance and social responsibility towards the environment. As technology develops, it will have an impact on the natural resources environment. If we do not limit the use of this technology, it will have a significant impact on natural resources. Green Computing is the right step to reduce CO2 emissions effectively. The research method was carried out by conducting literature studies from several journals (national and international) and taking the essence of the research. The type of data in this research uses secondary data, where data is obtained through electronic databases such as Google Scholar, Garuda (Digital Reference Guard), Sinta and from websites with high credibility on the internet that are appropriate to the topic being studied. The research results prove that the application of green computing can streamline and save electrical energy usage, reduce negative impacts on the environment and can extend the life of IT products.